2011
DOI: 10.1021/mp200137c
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Cells and Their Fibrotic Microenvironment Modulate Bone Marrow-Derived Mesenchymal Stromal Cell Migration in Vitro and in Vivo

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer and the third cause of cancer-related death. Fibrogenesis is an active process characterized by the production of several proinflammatory cytokines, chemokines and growth factors. It involves the activation of hepatic stellate cells (HSCs) which accumulate at the site of injury and are the main source of the extracellular matrix deposits. There are no curative treatments for advanced HCC, thus, new therapies are urgently needed. Mesenchymal stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 64 publications
8
57
2
Order By: Relevance
“…In line with others [60], we observed that conditioned medium from the human cell line Huh-7 was able to induce efficient migration in MSC similar to PDGF-BB, whereas conditioned medium from freshly isolated human hepatocytes and another hepatoma cell line, HepG2, did not. Therefore, the effect observed with the Huh-7 CM is specific to this type of cell line and is probably related to their unique secretory profile that we have analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…In line with others [60], we observed that conditioned medium from the human cell line Huh-7 was able to induce efficient migration in MSC similar to PDGF-BB, whereas conditioned medium from freshly isolated human hepatocytes and another hepatoma cell line, HepG2, did not. Therefore, the effect observed with the Huh-7 CM is specific to this type of cell line and is probably related to their unique secretory profile that we have analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…In vivo tracking of MSCs was performed as previously described [18]. In brief, MSCs were stained with CMDil for histological analysis and DiR (Molecular Probes, Invitrogen) for fluorescence imaging (FI).…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Once again MO-MSCs were shown to overexpress integrins that bind different collagens, including type I. Interestingly, both MD-MBA-231 breast cancer and A375N xenografts elicited an enhanced in vivo recruitment of MO-MSCs despite the fact that MDA-MB231 cells were not as efficient as melanoma cells to chemoattract MO-MSCs in vitro, suggesting that tumor-associated stromal cells might play a paracrine role in chemoattracting MO-MSCs in vivo. Further, the in vivo recruitment of MO-MSCs by experimental hepatocellular carcinoma was recently demonstrated by our group indicating that tumors with rather different types of stroma might all recruit MO-MSCs probably due to their enhanced capacity to adhere and migrate toward tumor stimulus [62]. Upon MO-MSCs systemic delivery, lungs and spleens showed minimal levels of engrafted MO-MSCs, with lung engraftment possibly related to initial microvascular trapping [63].…”
mentioning
confidence: 72%